Combustion and emission characteristics of diesel engine fueled with diesel/biodiesel/pentanol fuel blends. (15th September 2015) - Li, Li; Wang, Jianxin; Wang, Zhi; Xiao, Jianhua
Highlights: First study on combustion characteristic of diesel/biodiesel/pentanol with CI mode. Pentanol addition with diesel/biodiesel shows improved fuel/air mixing. Pentanol blends shows advanced CA50 and shorter combustion duration. Pentanol blends presents low emissions while maintaining higher ITE. Abstract: Pentanol is one of the next generation biofuels that could potentially help relieve the energy crisis and environmental problems. The objective of this study is to reveal the effects of pentanol addition to diesel and biodiesel fuels in different ratios on the combustion and emission of a single-cylinder direct-injection diesel engine. The tests were conducted at a constant speed (1600 r/min) under different engine loads without exhaust gas recirculation. The indicated thermal efficiency using pentanol blends was found to be higher than that of using pure diesel for all of tested loads from 0.5 to 1.0 MPa indicated mean effective pressure at the test conditions, which is due to its higher maximum heat release rate and shorter combustion duration. An obvious decrease in soot emissions was attained with the addition of pentanol. Moreover, emissions of nitrogen oxides (NO x ) were simultaneously reduced compared with using pure diesel fuel at low to middle loads. Furthermore, diesel engine fueled with oxygenated fuel blends can reduce the carbon monoxide and unburnt total hydrocarbons emissions except for the diesel–pentanol blends at low engine load. Finally, the strategy with 40% diesel–30% biodiesel–30% pentanol showed better combustion, emission characteristics as well as economy performance among all the fuels.